2022
DOI: 10.1038/s41467-022-31412-2
|View full text |Cite
|
Sign up to set email alerts
|

86Kr excess and other noble gases identify a billion-year-old radiogenically-enriched groundwater system

Abstract: Deep within the Precambrian basement rocks of the Earth, groundwaters can sustain subsurface microbial communities, and are targets of investigation both for geologic storage of carbon and/or nuclear waste, and for new reservoirs of rapidly depleting resources of helium. Noble gas-derived residence times have revealed deep hydrological settings where groundwaters are preserved on millions to billion-year timescales. Here we report groundwaters enriched in the highest concentrations of radiogenic products yet d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 74 publications
(346 reference statements)
0
28
0
Order By: Relevance
“…However, laboratory testing of core samples have found correlations between permeability and diffusion coefficients [37][38][39] . The lowest diffusion coefficients found in those studies were a few orders of magnitude higher than those required to prevent differential diffusion of Differential transport rates of different noble gases have been noted at Sudbury, Canada 2 and Moab Khotsong, South Africa 6 . In these studies the evidence for diffusive loss of the light noble gases (He, Ne) versus the heavier Ar, Kr, Xe was hypothesized to be related to increased fracturing of the basement due, in both cases, to their history as impact craters 5,6 .…”
Section: Constraining Permeability With Residence Time Estimatesmentioning
confidence: 83%
See 4 more Smart Citations
“…However, laboratory testing of core samples have found correlations between permeability and diffusion coefficients [37][38][39] . The lowest diffusion coefficients found in those studies were a few orders of magnitude higher than those required to prevent differential diffusion of Differential transport rates of different noble gases have been noted at Sudbury, Canada 2 and Moab Khotsong, South Africa 6 . In these studies the evidence for diffusive loss of the light noble gases (He, Ne) versus the heavier Ar, Kr, Xe was hypothesized to be related to increased fracturing of the basement due, in both cases, to their history as impact craters 5,6 .…”
Section: Constraining Permeability With Residence Time Estimatesmentioning
confidence: 83%
“…In this study the overall good coherence between the He-Ne-Ar-Xe derived noble gas residence times at each site support a model of hydrogeologic isolation. However, As Warr et al 2022 6 recently demonstrated, these settings actually represent a spectrum from being fully isolated to fully open. At sufficiently low diffusion coefficients (10 -15 m 2 /s), there will be no appreciable losses of any noble gases 29 .…”
Section: Constraining Permeability With Residence Time Estimatesmentioning
confidence: 99%
See 3 more Smart Citations